Pojęcie Ziemi Lubuskiej w ujęciu historycznym i politologicznym = A historical and political analysis of the Lubuskie Region as a concept - Halczak, Bohdan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The objective of this paper is to trace the historical origins of the region currently referred to as Ziemia Lubuska [the Lubuskie Region] and to delineate its territorial scope. The author demonstrates that the term was first employed by the authorities of the Poznań Voivodship in 1945 with reference to districts within the western and northern areas that had been incorporated into Greater Poland after World War II. Prior to 1945, most of these districts were part of the German region known as the "Neumark", or New March.
Keywords: Ziemia Lubuska; Nowa Marchia; biskupstwo lubuskie; Polska; Lubuskie Region; New March; Lubusz Bishopric; Poland